The Cross Ethnic Relationships in Strengthening Social Cohesion in Malaysia - Mak Din, Hairol Anuar; Hassan, Nor Azlili; Noor, Mansor Mohd (Universitas Ahmad Dahlan, 2019)
The foundation of developing a nation in Malaysia is based on the integration by which each ethnic identity is maintained and preserved within the Malaysian Federal Constitution. However, there is always a negative perception of the